An Assessment of Financial Monitoring Systems: Ukrainian and Foreign Experience - Hrytsyshen, Dymytrii; Hrabchuk, Iryna; Hrabchuk, Oleksandr; Ksendzuk, Valentyna; Lysak, Serhii (Comparative Economic Research. Central and Eastern Europe, 2024)
The study characterizes financial monitoring as part of the system for preventing and counteracting the legalization of income and the financing of terrorism. The purpose of the research is to study the experience of how national financial monitoring systems function (in the UK, USA, China, Georgia, Moldova, Pakistan, Poland and Ukraine) in order to determine development directions and identify implementation opportunities in domestic practice. The research methods include induction, analysis and synthesis, static, comparative and graphical methods. The research methodology is based on the analysis of official static data and information materials from the official websites of international organizations and competent national authorities. The article analyzes the statistical data of the state bodies of Ukraine in terms of their activities in the field of combating the financing of terrorism. It also constructs profiles to assess the effectiveness of anti‑money laundering systems as well as the handling of proceeds of crime and financing of terrorism in a number of countries, following the FATF (Financial Action Task Force) methodology. The results demonstrate that all national financial monitoring systems must comply with the requirements of the FATF. However, it is also necessary to consider the national characteristics of each country. Directions for further improvement of the financial monitoring system in Ukraine have been identified, i.e., enhance international cooperation, prevent the use of legal entities and organizations for criminal purposes, improve investigation and prosecution procedures for money laundering, especially considering international assistance received in the fight against Russian aggression, review investigation procedures and criminal prosecution in financing terrorism, and apply financial sanctions for the financing of terrorism.